2013
DOI: 10.1007/s10853-013-7333-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical shrinkage characterization techniques for thermoset resins and associated composites

Abstract: International audienceControl and optimization of curing process is very important for the production of high quality composite parts. Crosslinking of molecules of thermoset resin occurs in this phase, which involves exothermy of reaction, chemical shrinkage (Sh) and development of thermo-physical and thermo-mechanical properties. Exact knowledge of the evolution of all these parameters is required for the better understanding and improvement of the fabrication process. Sh is one such property of thermoset mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 97 publications
(118 reference statements)
1
40
1
Order By: Relevance
“…Volume dilatometry methods: capillary type dilatometer [3], plunger type dilatometer [4,5], and gravimetric method [6] Non-volume dilatometric methods: prepreg warpage [7], ultrasonic methods [8], curing thermoset films on the metal substrate [9], density gradient column technique [10], optical extensometer [11], and modified rheology method [12] A detailed review of the different techniques for shrinkage measurement can be found in the work by Nawab et al [13]. For the non-volume dilatometric methods, the polymer deformation is constrained during cure, so the knowledge of polymer modulus development is required to interpret shrinkage strains.…”
Section: Introductionmentioning
confidence: 99%
“…Volume dilatometry methods: capillary type dilatometer [3], plunger type dilatometer [4,5], and gravimetric method [6] Non-volume dilatometric methods: prepreg warpage [7], ultrasonic methods [8], curing thermoset films on the metal substrate [9], density gradient column technique [10], optical extensometer [11], and modified rheology method [12] A detailed review of the different techniques for shrinkage measurement can be found in the work by Nawab et al [13]. For the non-volume dilatometric methods, the polymer deformation is constrained during cure, so the knowledge of polymer modulus development is required to interpret shrinkage strains.…”
Section: Introductionmentioning
confidence: 99%
“…capillary dilatometer, gravimetric method, rheometer, and thermo-mechanical analyzer) have been proposed and utilized to characterize and model cure shrinkage of thermoset resins and their composites. 4 However, most of the instruments work under conditions that do not match practical processes (e.g. in a high-pressure autoclave).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Optical-fiber sensors are highly sensitive and very thin (diameter less than 150 mm), and thus can be embedded in composite materials in a minimally invasive manner and without significant effects on the global mechanical behavior of the host material. Several studies utilized fiber-optic sensors for in situ process monitoring of thermosetting resins 7-10 and their composites.…”
Section: Introductionmentioning
confidence: 99%
“…As no precise value was available in the literature, average values were chosen from the different studies concerning the development of mechanical properties of epoxy resins during cure. 3,[6][7][8][9][10][11][12][13][14]16,[24][25][26][27][28][29] Also, the different mechanical properties generally depend on the temperature, which is due to a modification of the molecular agitation as the temperature changes. As will be shown later, the chemical reaction happens during an isothermal step.…”
Section: Rtm6 Epoxy Resinmentioning
confidence: 99%